Analisis Efektivitas Implementasi Sustainable Development Goals ke-9 dalam Industrialisasi Pertanian di Rwanda - Alfin Febrian Basundoro; Allysa Ramadhani (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2020)
Africa has great potential for development with its human and natural resources potential. Many African countries, including Rwanda, have protractedly relied on agriculture as their main source of income; however, the agricultural sector within the region has not faced thorough development due to, for example, limited progress in both agroindustries and agribusiness. Supported by technology and human resources development, global agriculture has progressed rapidly, and agriculture has become a strategic aspect of several national policies. In addition, several international institutions—such as the United Nations (UN), Food and Agriculture Organization (FAO), and United Nations Industrial Development Organization (UNIDO) —have formed various frameworks related to the sector. Utilizing approaches that address problems of human security and food security, this paper explains whether Rwanda’s agricultural industrialization methods are in line with both the four FAO-UNIDO agricultural industrialization pillars and also the ninth Sustainable Development Goals on infrastructure, industry, and innovation